2007
DOI: 10.1016/j.juro.2007.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Renal Access by Urologist or Radiologist for Percutaneous Nephrolithotomy—Is it Still an Issue?

Abstract: The urologist is able to safely and effectively obtain percutaneous renal access for percutaneous nephrolithotomy as a single stage procedure. Despite more complex stones and higher access difficulty in the urology access group, access related complications and stone-free rates were comparable. We recommend percutaneous access training in urology training programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
55
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 19 publications
2
55
0
1
Order By: Relevance
“…Only 11% of urologists routinely perform percutaneous puncture without the assistance of a radiologist (5). Access obtained by interventional radiologists is comparable to that obtained by urologists, but additional studies have shown that the stone-free rate is higher and access-related complications were less frequent when access is obtained by a urologist (5,11,12). This difference in rates may be because urologists aim to obtain direct access into a renal calyx to reach the stone, whereas radiologists often place percutaneous access for drainage only.…”
Section: Discussionmentioning
confidence: 99%
“…Only 11% of urologists routinely perform percutaneous puncture without the assistance of a radiologist (5). Access obtained by interventional radiologists is comparable to that obtained by urologists, but additional studies have shown that the stone-free rate is higher and access-related complications were less frequent when access is obtained by a urologist (5,11,12). This difference in rates may be because urologists aim to obtain direct access into a renal calyx to reach the stone, whereas radiologists often place percutaneous access for drainage only.…”
Section: Discussionmentioning
confidence: 99%
“…This is despite the fact that the literature shows that urologist-directed percutaneous nephrostomy placement is very safe and effective with failure rates and complications rates comparing favourably with radiology colleagues. 1,5,6 This novel set up has resulted in several improvements to the service we offer patients as well as providing increased exposure for our trainees to renal ultrasound and percutaneous nephrostomy placement. Although we acknowledge the numbers of nephrostomies and anterograde stents we have performed is still relatively small, the experience gained by our trainees in these procedures is invaluable and not available readily in other urology departments to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…This is despite good evidence that urologists can safely and effectively obtain percutaneous renal access with comparable outcomes to radiologists. 1 Radiologists also carry out numerous nephrostograms and nephrostomy removals under fluoroscopy in patients with concurrent JJ stents to avoid the stent being inadvertently displaced. This is a heavy burden on interventional radiology lists, which are already oversubscribed.…”
mentioning
confidence: 99%
“…With numerous previous studies, pre-and peri-operative factors such as stone size and configuration, percutaneous access number and location, entry performed by radiologist or urologist, presence of hydronephrosis have been investigated as predictors of success rates and complications [4][5][6][7][8][9][10]. Attempts to identify the associated variables showed variations among the results which has made it difficult to classify the patients so that the stone free rate (SFR) or complications can be predicted.…”
Section: Introductionmentioning
confidence: 99%